Karakter Entrepreneur Dalam Sudut Pandang Islam - Herningrum, Indah; Alfian, Muhammad; Putra, Pristian Hadi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Islam is the most perfect religion. One of the perfections of Islam is to oblige all Muslims to earn a lawful living by working or doing business in the right way. Islam not only teaches to worship, but Islam also teaches its people to be independent and work hard. One of them with entrepreneurship or Entrepreneurship. This paper aims to see that the importance of having an entrepreneurial character is seen from the nature of entrepreneurship, how the character of entrepreneurship is from an Islamic point of view, then wants to see the supporting factors and driving factors for entrepreneurial activities for the advancement of economic development in Indonesia. This study collects as much data as possible from primary data sources, namely entrepreneurship books. And secondary data in the form of journals and books that discuss entrepreneurial theory from an Islamic perspective. The technique of data analysis is done by annotated bibliography analysis (annotated bibliography) which means a simple conclusion from an article, book, journal. Entrepreneurship according to Islamic teachings is a job that requires hard work. While working hard is an obligation for every Muslim. The entrepreneurial character in Islam is taqwa, honest and trustworthy, prioritizing the concept of halal, the command to work hard. The driving factors for entrepreneurship are having the ability and willingness, strong determination and hard work, opportunities and opportunities. While the inhibiting factors for entrepreneurship are managerial incompetence, lack of experience, both in technical skills, visualizing businesses, organizing, managing human resources and integrating business operations, lack of financial control, failure in site planning, and lack of equipment supervision.